2005
DOI: 10.1183/09031936.05.00104504
|View full text |Cite
|
Sign up to set email alerts
|

The effects of body weight on airway calibre

Abstract: Increased wheeze and asthma diagnosis in obesity may be due to reduced lung volume with subsequent airway narrowing.Asthma (wheeze and airway hyperresponsiveness), functional residual capacity (FRC) and airway conductance (Gaw) were measured in 276 randomly selected subjects aged 28-30 yrs. Data were initially adjusted for smoking and asthma before examining relationships between weight and FRC (after adjustment for height), and between body mass index (BMI5 weight?height -2 ) and Gaw (after adjustment for FRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
1
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 29 publications
7
113
1
9
Order By: Relevance
“…The difference in reactance between obese and non-obese subjects is in keeping with other evidence that suggests that there are differences in respiratory system mechanics that are not reflected in FEV 1 . 12 Obesity and asthma Our findings suggest a mechanism whereby asthma might be induced in obese subjects, in the absence of any direct effects of obesity on AHR. It has been suggested that the excess wheezing illness in the obese is not due to 'real' asthma, but is simply a misdiagnosis of excessive breathlessness.…”
Section: Perception Of Dyspneamentioning
confidence: 74%
See 1 more Smart Citation
“…The difference in reactance between obese and non-obese subjects is in keeping with other evidence that suggests that there are differences in respiratory system mechanics that are not reflected in FEV 1 . 12 Obesity and asthma Our findings suggest a mechanism whereby asthma might be induced in obese subjects, in the absence of any direct effects of obesity on AHR. It has been suggested that the excess wheezing illness in the obese is not due to 'real' asthma, but is simply a misdiagnosis of excessive breathlessness.…”
Section: Perception Of Dyspneamentioning
confidence: 74%
“…10,11 Previous studies of the association between obesity and AHR have measured effects on sensitivity. [3][4][5][6][7] However, obesity is more likely to affect the maximal response, because obesity reduces operating lung volume 12 and breathing at low operating lung volumes is known to induce increased maximal airway narrowing in non-asthmatic subjects. 13,14 The effect of low lung volume on maximal airway narrowing in obese, non-asthmatic subjects has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms have been suggested, including the possibility that abdominal fat deposition leads to a redistribution of blood to the thoracic compartment that reduces vital capacity (Harik-Khan et al, 2001). In addition, high amounts of FM may be related to a greater degree of airway narrowing than would be expected on the basis of reduced lung volume alone, although the mechanisms remain uncertain (King et al, 2005). However, obesity is a complex disorder and the effects of excess adipose tissue on pulmonary function may be influenced by the location of excess fat deposits as well as by their extent.…”
Section: Discussionmentioning
confidence: 99%
“…In obese males, airway narrowing seems to be greater than what would be expected to result from reduced lung volume alone. (20) In populationbased studies, asthma has been associated with obesity, especially in females. (21) In individuals with asthma, the increase in RV is greater than the decrease in FVC, due to a simultaneous increase in TLC.…”
Section: Discussionmentioning
confidence: 99%